The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4081/ejh.2021.3322
|View full text |Cite
|
Sign up to set email alerts
|

The possible alleviating effect of garlic supplement on the neural retina in a rat model of hypercholesterolemia: a histological and immunohistochemical study

Abstract: The purpose of this work was to prove that oxidative stress is the main mechanism responsible for retinal neurodegenerative changes, subsequent apoptosis, and inflammatory cytokine release in rats fed with a high cholesterol diet (HCD) and determine the role of garlic in alleviating these changes. Forty rats were equally divided into four groups: control, garlic-treated (positive control), HCD, and HCD + garlic-treated (HCD + G). By the end of the experiment (24 weeks) blood samples were collected for assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…On the other hand, the increase in optic nerve blood flow is reported to have a pivotal role in the improvement of visual acuity in glaucoma patients [ 36 ]. Garlic is also demonstrated to ameliorate the process of neurodegeneration of the neural retina in animal models [ 37 ], which might support our finding. Given that ocular ischemia due to vascular endothelium damage is the main cause of diabetic retinopathy and damage to the neural retina, it is suggested that garlic intake might improve visual acuity by increasing the ocular blood flow and protecting the neural retina from oxidant stress.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, the increase in optic nerve blood flow is reported to have a pivotal role in the improvement of visual acuity in glaucoma patients [ 36 ]. Garlic is also demonstrated to ameliorate the process of neurodegeneration of the neural retina in animal models [ 37 ], which might support our finding. Given that ocular ischemia due to vascular endothelium damage is the main cause of diabetic retinopathy and damage to the neural retina, it is suggested that garlic intake might improve visual acuity by increasing the ocular blood flow and protecting the neural retina from oxidant stress.…”
Section: Discussionsupporting
confidence: 88%
“…Dyslipidemia is one of the strong predisposing factors for developing cardiovascular disorders (Coenen et al, 2021). Cardiovascular disorders are the leading cause of mortality and morbidity worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…These phenolic compounds also play an important role in regulating lipid metabolism and cholesterol synthesis, so figs act as anti-dyslipidemic agents (Russo et al, 2014). Garlic (Allium Sativum) is one of the natural plants or herbs used for treating hypercholesterolemia for many centuries (Arafat et al, 2021). In the Roman Empire, garlic consider a drug of choice for cardiac problems and skin problems (Elkordy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garlic was obtained from ATOS Pharma (Cairo, Egypt) as Tomex Plus tablets (300 mg dried garlic powder). Garlic tablets were crushed, dissolved in normal saline, and was administered at dose 200 mg/kg body weight according to Arafat et. al., (2021).…”
Section: Chemicalsmentioning
confidence: 99%